2006
DOI: 10.1097/01.hjh.0000220403.61493.18
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting angiotensin type 1 receptor binding and protection by candesartan: comparison with other biphenyl-tetrazole sartans

Abstract: Slow receptor dissociation and slow antagonist elimination are likely to act in synergy to produce long-lasting receptor protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Such non-equilibrium single-point measurements do not capture the actual kinetics by which the small molecule binds to and, most importantly, subsequently resides on the human CRF 1 receptor in vivo (Fleck et al, 2012; Ramsey et al, 2011). Greater receptor antagonist efficacy is putatively associated with greater residence time on the receptor (Brinkerhoff et al, 2008; Fleck et al, 2012; Tummino and Copeland, 2008; Vauquelin et al, 2006; Vauquelin and Van Liefde, 2006), as exemplified in the greater efficacy and duration of action of candesartan, a slowly dissociating angiotensin II AT1 receptor antagonist (Lacourciere and Asmar, 1999; Verheijen et al, 2004), versus the more rapidly dissociating antagonist losartan (Hansson, 2001). Kinetic analysis of receptor association and dissociation rates at physiological temperatures demonstrated that R121919, with which positive preliminary clinical findings were obtained, exhibits a “kinetic” K i of ~0.36 nM, a potency underestimated by binding constants for it of 3–4 nM in standard competition assays (Fleck et al, 2012).…”
Section: Nonpeptide Crf1-selective Receptor Antagonistsmentioning
confidence: 99%
“…Such non-equilibrium single-point measurements do not capture the actual kinetics by which the small molecule binds to and, most importantly, subsequently resides on the human CRF 1 receptor in vivo (Fleck et al, 2012; Ramsey et al, 2011). Greater receptor antagonist efficacy is putatively associated with greater residence time on the receptor (Brinkerhoff et al, 2008; Fleck et al, 2012; Tummino and Copeland, 2008; Vauquelin et al, 2006; Vauquelin and Van Liefde, 2006), as exemplified in the greater efficacy and duration of action of candesartan, a slowly dissociating angiotensin II AT1 receptor antagonist (Lacourciere and Asmar, 1999; Verheijen et al, 2004), versus the more rapidly dissociating antagonist losartan (Hansson, 2001). Kinetic analysis of receptor association and dissociation rates at physiological temperatures demonstrated that R121919, with which positive preliminary clinical findings were obtained, exhibits a “kinetic” K i of ~0.36 nM, a potency underestimated by binding constants for it of 3–4 nM in standard competition assays (Fleck et al, 2012).…”
Section: Nonpeptide Crf1-selective Receptor Antagonistsmentioning
confidence: 99%
“…Yet, there is increasing awareness that the time period over which they reside at their target also affects their clinical performance [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Examples of such slow-dissociating drugs have been enumerated and commented on in recent dedicated review articles [4,5,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…8 In vitro studies have shown that candesartan acts as an insurmountable antagonist and is able to virtually eliminate the AT 1 receptor-mediated effects of angiotensin II. 9 Compared with other widely used ARBs, candesartan shows high binding affinity for the AT 1 receptor, 9 that is, B80-fold higher than losartan and 10-fold higher than EXP 3174. Insurmountable antagonism provides long-lasting suppression of the reninangiotensin-aldosterone system, and it is suggested that this accounts for the magnitude of the antihypertensive efficacy of candesartan and for its sustained duration of effect.…”
Section: Introductionmentioning
confidence: 99%